Matching and saving in continuous time: Proofs - Christian Bayer; Klaus Wälde (Center for Economic Studies and ifo Institute (CESifo), 2010)
This paper provides the proofs to the analysis of a continuous time matching model with saving in Bayer and Wälde (2010a). The paper proves the results on consumption growth, provides an existence proof for optimal consumption and a detailed derivation of the Fokker-Planck equations.
Keywords: C62; C65; 330; continuous time uncertainty; Fokker-Planck equation; existence proof; Sparen; Zeitpräferenz; Optimaler Konsum; Euler-Gleichung; Stochastischer Prozess; Theorie